2021
DOI: 10.32794/mr11250096
|View full text |Cite
|
Sign up to set email alerts
|

Melatonergic index as a prognostic biomarker of reproductive organ cancers: correlations with metabolic parameters as well as clock genes PER1 and TIMELESS

Abstract: Cancers of the reproductive organs are often hard to be detected, and patients’ survival rate drops considerably even when the tumor is removed. Based on the fact that melatonin levels are significantly lower in cancer cells than that in the healthy cells, and this melatonin suppression remains during tumor progression, we have examined a simple two-gene-based melatonergic system [the indices of melatonin synthesis and metabolism (ASMT:CYP1A1, ASMT:CYP1A2, ASMT:CYP1B1)] as a prognostic factor for reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Treatment of uterine endometrial cancer cells with melatonin halts tumor progression through SDH inhibition [ 44 ]. Moreover, we previously reported that female reproductive organ tumors exhibit a positive correlation of ASMT with OXPHOS-related enzymes including PDHA1 and SDHB [ 45 ]. Mitochondria have the machinery responsible for the conversion of redox energy into an electrochemical gradient and the production of ATP formed in ETC through ATP synthase [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of uterine endometrial cancer cells with melatonin halts tumor progression through SDH inhibition [ 44 ]. Moreover, we previously reported that female reproductive organ tumors exhibit a positive correlation of ASMT with OXPHOS-related enzymes including PDHA1 and SDHB [ 45 ]. Mitochondria have the machinery responsible for the conversion of redox energy into an electrochemical gradient and the production of ATP formed in ETC through ATP synthase [ 46 ].…”
Section: Discussionmentioning
confidence: 99%